Unusual rare case of Plasmodium vivax presenting with anemia, thrombocytopenia, and jaundice (Indian Journal of Case Reports, 2025)
Plasmodium vivax is the second most common cause of malaria globally and the primary cause of malaria outside of Africa. The difficulties in controlling and eradicating vivax malaria are likely linked to specific biological characteristics of P. vivax: (a) its capacity to relapse from long-lasting dormant liver stages known as hypnozoites, and (b) its significant transmission potential, which arises from the early and continuous production of gametocytes, high infectivity, and a shorter developmental cycle in the vector compared to other Plasmodium species. Anemia, thrombocytopenia, jaundice, and central nervous system manifestations are commonly found in Falciparum malaria, whereas these are very rare in vivax malaria. We present a rare and unusual presentation of P. vivax malaria in a 31-year-old male from Sitapur, Uttar Pradesh, where the patient exhibited anemia, thrombocytopenia, and jaundice.